24.3k views
25 votes
Which expression is equivalent to (2x + 6) - (3x + 4)

A. -1x + (10)
B. 5x + (10)
C. -1x + (2)
D.5x + (-2)

User Yang Meyer
by
5.1k points

2 Answers

3 votes

Answer:

C

Explanation:

Expand the brackets = 2x + 6 - 3x - 4

Take 3x from 2x to get -1x

The equation is now -1x + 6 - 4

Take 4 from 6 to get 2

The equation is now -1x + 2, which is equal to option C

User Andrsmllr
by
5.4k points
12 votes

Answer:

C. -1x + (2)

Explanation:

(2x + 6) - (3x + 4)

= 2x + 6 -3x - 4

= 2x - 3x + 6 - 4

= -1x +2

User AndSmith
by
4.8k points